Obtenção e funcionalização da superfície da zeólita FAU particulada e imobilizada em fibras de PLA para a adsorção de corantes - Mascarenhas, Bruno Cano (Universidade Federal de São Carlos, 2017)
The importance given to the environmental issue leads us to promote the search for resources that minimize the degradation of the environment, especially with respect to water resources area. In this context, there is a growing development of water treatment methods that promote the efficient removal of pollutants, among which, the adsorption process. The major problem in the use of adsorbents is adequate immobilization, which provides the removal and reuse of these compounds. Thus, the present work had the objective of obtaining FAU zeolite and PLA:FAU composite and evaluation of the adsorption capacity of dyes (Rhodamine B and Methylene blue) in aqueous medium. The zeolite particles were synthesized by the hydrothermal method and the PLA: FAU composite was obtained by the electro-spinning technique. The zeolite was functionalized using mercaptopropyltrimethoxysilane (MPTS) to increase surface hydrophobicity. The hydrophobic material was evaluated for the adsorption of dyes in aqueous medium, presenting efficiency higher than 90% for both dyes analyzed. With respect to the PLA: FAU composite, uniform fibers were obtained with addition of 20% FAU (in mass), with good distribution of the particles on the polymer matrix. The adsorption tests using the composite reveal that the material is promising for the removal of dyes in the aqueous medium by the adsorption process, maintaining efficiencies above 80% for rhodamine B and 90% for methylene blue after 90 min. The impregnation of Faujasite in PLA matrix allowed the applicability of the material as a potential adsorbent, because unlike the dispersed particulate in solution, it is easily removed from the medium by mechanical forces
Synthesis and functionalization of the FAU Zeolite surface and immobilization in PLA fibers for dyes adsorption
Keywords: Nanopartículas; Adsorção; Funcionalização; Faujasita; Tratamento Hidrotérmico; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA